Upaya Penanganan Dismenorea Berbasis Thibbun Nabawi Pada Remaja - Winarni Winarni; Ai Rahmawati; Hasanah Hasanah; Wahyu Atika Putri (PPNI UNIMMAN, 2023)
Dysmenorrhoea is experienced by 90% of women in Indonesia, because of this, around 14% of women cannot participate in learning at school or carry out daily activities, thereby reducing their productivity. Adolescent girls are in an unstable emotional condition, if they do not get good information about the menstrual cycle then they are easy to experience primary menstrual disorders. Primary dysmenorrhea is experienced by many teenagers who are growing and developing both physically and psychologically. Several efforts have been made to reduce pain complaints in cases of dysmenorrhoea, including non-pharmacological intervention, including Rosulullah-style treatment, known as Thibbun Nabawi treatment, including listening to the Koran and breathing exercises, this treatment is cheap and can be done independently by everyone. people who experience it. The implementation of socialization at Al Islam High School is really needed considering that in this school there are many cases of Dysmennorrhea, and no one has provided an understanding of these cases and how to manage them non-pharmacologically so that they can be overcome without causing side effects. The target of this community service proposal is Al Islam Surakata High School students. The benefit of this activity is to increase understanding about menstrual disorders, especially dysmenorrhea and treatment of pain complaints when dysmenorrhea occurs at low cost and without side effects. impact, namely by means of Tibbun Nabawi.”